2020
DOI: 10.3897/mycokeys.69.51652
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Perenniporia (Polyporales, Basidiomycota)

Abstract: Two new species of Perenniporia, P. pseudotephroporasp. nov. and P. subcorticolasp. nov., are introduced respectively from Brazil and China based on morphological characteristics and molecular data. Perenniporia pseudotephropora is characterised by perennial, pileate basidiocarps with distinctly stratified tubes, grey pores, tissues becoming dark in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Notes: Xanthoperenniporia maackiae grows mainly on Maackia . Xanthoperenniporia subcorticola is similar to X. maackiae by sharing resupinate basidiocarps with yellow pore surfaces, similar sized pores, and the presence of cystidioles, but X. subcorticola has smaller basidiospores (4.2–5 × 3.5–4.2 µm) [ 29 ], and X. maackiae has larger basidiospores (5.4–6.3 × 3.8–5.0 µm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notes: Xanthoperenniporia maackiae grows mainly on Maackia . Xanthoperenniporia subcorticola is similar to X. maackiae by sharing resupinate basidiocarps with yellow pore surfaces, similar sized pores, and the presence of cystidioles, but X. subcorticola has smaller basidiospores (4.2–5 × 3.5–4.2 µm) [ 29 ], and X. maackiae has larger basidiospores (5.4–6.3 × 3.8–5.0 µm).…”
Section: Resultsmentioning
confidence: 99%
“…Notes: Xanthoperenniporia subcorticola was recently described in Perenniporia as P. subcorticola Chao G. Wang & F. Wu by Wang et al [ 29 ]. It is similar to Perenniporia corticola by having a yellow pore surface, dimitic hyphal system, and truncate and dextrinoid basidiospores of almost the same size, but P. corticola differs from P. subcorticola by having arboriform skeletal hyphae and dendrohyphidia [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR program was performed with an initial temperature at 95 °C for 5 min, then 30 cycles of denaturation at 95 °C for 60 s, annealing at 55 °C for 45 s and extension at 72 °C for 60 s, and finally an extra extension at 72 °C for 10 min. The PCR product was sequenced with the primer LR5M, as well as ITS4 (5′-TCC TCC GCT TAT TGA TAT GC-3′) and ITS5 (5′-GGA AGT AAA CGT AAC AAG G-3′) [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…All positive isolates in this study, except Deconica, are white rot-fungi. Most white-rot fungi have been used widely as dye-degrading fungi (Wang et al 2018(Wang et al , 2020. Hefnawy et al (2017) reported that the boundary of the decolorization zone in the solid medium could not be determined significantly at higher dye concentrations.…”
Section: Laccase Activitymentioning
confidence: 99%